Divisional Informativeness Gap and Value Creation from Asset Sales. Issue 4 (November 2016) - Desai, Chintal A.; Gupta, Manu
Abstract: Nanda and Narayanan (1999) show that the information asymmetry between the managers and market participants regarding divisional cash flows helps explain the value creation on asset sales. Based on their theoretical framework, the divisional informativeness gap hypothesis predicts that the announcement‐period return increases with the difference in cash‐flow informativeness of retained and divested divisions prior to the divestiture. Our results, using industry‐average earnings response coefficient as a proxy for cash‐flow informativeness of a division, support this prediction. The effect is stronger when a conglomerate retains the division with relatively greater growth opportunities.